A social constructionist approach to teaching and learning vocabulary for Italian for academic purposes - Xerou, Eftychia; Papadima-Sophocleous, Salomi; Parmaxi, Antigoni (My University, 2016)
This study presents the way Parmaxi and Zaphiris’s (2015) social constructionist framework was used in order to teach and learn vocabulary in an Italian for Specific Academic Purposes (ISAP) tertiary course. The participants (beginner students) were guided to build in groups an artifact, i.e a specific academic vocabulary collection. To do so, they used Quizlet; this online learning tool allows the creation of digital artifacts, such as vocabulary flashcards, games and quizzes, and the sharing of the collections created. The purpose of the creation of the artifact was the learning and sharing of vocabulary in Italian used in the specific area of the students’ university fields of study. The data revealed that the social constructionist approach facilitated a more engaged and motivating attitude towards learning, allowing students to work constructively and collaboratively and share their knowledge with the use of new technologies.
Keywords: Vocabulary; Italian for specific purposes; Constructionism; Quizlet